Evaluation of the use of reactive oxygen species (ROS) generated through oxyion® technology in strawberry (Fragaria × ananassa (Duchesne ex Weston) Duchesne ex Rozier cv. Monterrey) storage (2018)
Reactive oxygen species (ROS) play a key role in oxidative stress processes at the biological level. In most cases the presence of these chemical species is undesirable due to the impact they have on tissues and cellular structures, however, their effects can be used to control the incidence of microorganisms responsible for deterioration processes in fruits and vegetables. In the present study the feasibility of combining low temperature storage with the presence of reactive oxygen species generated using Oxyion® technology to control the deterioration process in strawberry (Fragaria X ananassa) was studied. The treatments used were as follows: control storage (4°C ± 2°C without Oxyion®) and ROS storage (4°C ± 2°C with Oxyion®), for two product categories according to weight and maturation state according to NTC 4103 (ICONTEC, 1997). The variables were monitored with measuring points at 1, 3, 5, 7, 10 and 15 days after harvest in percentage of loss of mass, soluble solids, respiratory intensity, acidity, resistance, color and ethylene and significant interactions among variables. At the conclusion of the study, Oxyion® technology was found to have statistically significant differences compared to control, and have allowed to less weight loss, higher resistance and lower exogenous ethylene production, extending the life of strawberry cv. Monterrey in a 40% during storage, additionally the losses by action of microorganisms present in strawberries surface were reduced considerably, generating a positive precedent in the processes of storage and conservation of fruits for Colombia.